2018
DOI: 10.2139/ssrn.3257093
|View full text |Cite
|
Sign up to set email alerts
|

Present Bias and Financial Behavior

Abstract: Present bias is an important term in the theory of self-control in behavioral finance. Empirical research finds that present bias is associated with undesirable spending, borrowing, and saving behaviors. Unlike previous research that focuses on one domain of financial behavior, the purpose of this study is to examine associations between present bias and a set of financial behaviors in various domains: spending, borrowing, saving, and money management. With data from a national urban sample in China, results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This has been demonstrated by Meier and Sprenger (2010) regarding credit card debt, while Brown and Previtero (2015) showed that present‐biased individuals were less likely to annuitize in defined benefit pension plans. Xiao and Porto (2019) examined the relationship between present bias and expenditure patterns in China and concluded that the present biased tended to spend more impatiently. In line with this literature, our analysis also elicits respondents' impatience levels and relates it to their vulnerability to financial shocks.…”
Section: Prior Literaturementioning
confidence: 99%
“…This has been demonstrated by Meier and Sprenger (2010) regarding credit card debt, while Brown and Previtero (2015) showed that present‐biased individuals were less likely to annuitize in defined benefit pension plans. Xiao and Porto (2019) examined the relationship between present bias and expenditure patterns in China and concluded that the present biased tended to spend more impatiently. In line with this literature, our analysis also elicits respondents' impatience levels and relates it to their vulnerability to financial shocks.…”
Section: Prior Literaturementioning
confidence: 99%
“…PFMB can differ between population sub-groups according to marital status, income, occupation, gender, education and family structure (Perry and Morris, 2005;Grable et al, 2009;Loke 2017a;Sachitra et al, 2019;Bapat, 2020). In comparison to the work done on demographics and socio-economic factors, research on psychological factors underlying personal financial planning behavior is in an elementary stage (Joo and Grable, 2004;Xiao and Porto, 2019). Based on the existing body of literature, various psychological factors have been accounted for.…”
Section: Antecedents Of Pfmbmentioning
confidence: 99%
“…This pilot questionnaire has a validity score of 0.86 and a reliability score of 0.77. Financial management behavior is measured in four aspects, including spending, borrowing, saving, and money management [18]. Variables were evaluated on a 5-point scale to determine their impact on behavior.…”
Section: Methodsmentioning
confidence: 99%
“…The trait of seeking current pleasure at the cost of future rewards is known as present bias. It is defined as overvaluing current advantages at the expense of future returns [18]. Those who are more present-biased are more prone to consuming rather than saving and investing their money in terms of current and future expenditures.…”
Section: Present Bias Nudges and Financial Knowledgementioning
confidence: 99%